2016
DOI: 10.1111/boc.201500063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the scaffold proteins liprin‐α1, β1 and β2 on invasion by breast cancer cells

Abstract: Our results indicate the importance of liprins in breast cancer cell invasion, and are expected to lead to future investigations on the mechanisms underlying the effects of distinct liprin proteins in different processes linked to tumor cell migration and invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 27 publications
2
44
0
Order By: Relevance
“…Secretory trafficking delivers to the cell surface membrane type 1 metalloprotease (MT1-MMP), which can degrade the extracellular matrix around FAs, resulting in integrin detachment, loss of tension, and FA turnover 116 . These observations help to explain why liprin-α1, liprin-β1, LL5β, and ELKS promote invasive behavior and internalization of integrins in breast cancer cells 86, 88, 117119 . Importantly, MT1-MMP delivery and integrin recycling also strongly depend on endosomal trafficking, which requires microtubules (for review, see 120, 121).…”
Section: Clasp- and Ll5-associated Complexes In Microtubule Organizatmentioning
confidence: 75%
“…Secretory trafficking delivers to the cell surface membrane type 1 metalloprotease (MT1-MMP), which can degrade the extracellular matrix around FAs, resulting in integrin detachment, loss of tension, and FA turnover 116 . These observations help to explain why liprin-α1, liprin-β1, LL5β, and ELKS promote invasive behavior and internalization of integrins in breast cancer cells 86, 88, 117119 . Importantly, MT1-MMP delivery and integrin recycling also strongly depend on endosomal trafficking, which requires microtubules (for review, see 120, 121).…”
Section: Clasp- and Ll5-associated Complexes In Microtubule Organizatmentioning
confidence: 75%
“…Matrix composition, stiffness, diffusion limitations, and vasculature are the primary contributors to drug resistance caused by the physical attributes of the ECM. In the case of CAM‐DR, the binding of cancer and/or stromal cells to ECM ligands such as collagens and fibronectin alters the mechanical properties of the matrix and can activate pro‐survival pathways, most commonly mediated by β1 integrins (Chiaretti, Astro, Chiricozzi, & de Curtis, 2016; Dittmer & Leyh, 2015; Park et al, 2006). SFM‐DR is caused by growth factors, proteins, proteases, and cytokines secreted by cancer‐associated fibroblasts (CAFs), mesenchymal stem cells (MSCs), or tumor‐associated macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…The mammalian liprin family includes four liprin-α (liprin-α1 to -α4) proteins and two liprin-β (β1 and β2) proteins [8], which together form heterodimers and act as scaffolds [9]. A number of recent studies have revealed broader functions of the liprin family in regulating the development and homeostasis in other organs, including the mammary gland and lymphatic vessel [10,11]. Notably, analysis of human cancers has revealed dysfunctions of the liprin proteins, with evidence pointing to the different roles of liprin family members in distinct aspects of tumor biology.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, analysis of human cancers has revealed dysfunctions of the liprin proteins, with evidence pointing to the different roles of liprin family members in distinct aspects of tumor biology. For example, overexpression of liprin-α1 promotes breast cancer cell invasion by regulating lamellipodia stability and integrin-mediated focal adhesions [10,12]. By contrast, liprin-β2 impairs cell motility and suppresses tumor invasion, which is indicative of its role as a tumor suppressor [10].…”
Section: Introductionmentioning
confidence: 99%